Biosensors for the Environmental Monitoring of Aquatic Systems Bioanalytical and Chemical Methods for Endocrine Disruptors - Barceló, Damià; Hansen, Peter-Dietrich (Water Pollution ;, 2009)
There is an increasing need for effective methods of estimating the risks caused by the large number of pollutants released into the environment by human activities. This volume provides an overview of biosensors as a key tool for the environmental monitoring of aquatic systems. Biosensor technology is based on a specific biological recognition element in combination with a transducer for signal processing. In particular, the detection and identification of endocrine-disrupting compounds and other toxins in wastewater are treated in detail. Biosensors are presented as a practical alternative or supplement to traditional chromatographic techniques. Emphasis is also placed on the validation of the applied technology and its application to real-world environmental samples.